Living Hadith: The Art of Jathilan Suryo Budoyo as a Media for Da'wah: Roland Barthes' Semiotic Analysis - Arhanudri Davi Mawarni; Zainudin, Zainudin; Restendy, Mochammad Sinung (Yayasan Darussalam Bengkulu, 2026)
Art is an integral part of Indonesian society. Through art, various meanings or messages can be effectively conveyed. The role of art has a positive impact on the development of da'wah (Islamic propagation) in this country. One such art form is the Suryo Budoyo jathilan (jathilan dance). The purpose of this study is to examine the art form